Photo-, radio- and thermoluminescence of Sm3+ doped and Tb3+/Sm3+ doubly doped K2YF5 single crystals - Marcazzo, Salvador Julian (2013)
Photoluminescence, radioluminescence and thermoluminescence properties of K2YF5 crystals containing different concentrations of samarium and terbium ions have been investigated for the first time. It has been found that the emission peaks observed in ranges from 300 to 550 nm and from 550 to 750 nm can be attributed to the 4f–4f transitions of the Tb3+ ions and the Sm3+ ions, respectively, for both photoluminescence and radioluminescence. The maximum of light output for radioluminescence under beta irradiation has been obtained for K2YF5 crystals doped with 1.0 at% Sm3+ ions and the prospects for using such dosimeters in fiber optic dosimetry have been evaluated. On the other hand, it has been found that the glow curves of doubly doped fluoride crystals are made up of at least four overlapping glow peaks and that K2YF5:1.0 at% Tb3+; 0.5 at% Sm3+ crystals show the most intense thermoluminescence emission.